Supplements to the Atlas of Butterflies (Lepidoptera: Rhopalocera) of Slovenia - Čelik, Tatjana (Hacquetia, 2015)
The Atlas of butterflies (Lepidoptera: Rhopalocera) of Slovenia (Verovnik et al. 2012) treats 179 butterfly species whose occurrence in Slovenia is confirmed, and 24 species for which only unconfirmed data exist. By the end of 2011, 212.936 distribution records by 167 contributing authors were collected for the Atlas. The Digital database of butterflies of the Jovan Hadži Institute of Biology of the Scientific Research Centre of the Slovenian Academy of Sciences and Arts was not considered in the process of collecting the data for the Atlas. This database contains 30.630 distribution records for butterfly species found in Slovenia from research projects undertaken by the Institute from 1995 to date. Given that this rich data source was not included in the Atlas, I here provide a supplement to the existing Atlas, reporting 1529 new records for 140 butterfly species. These updates provide new areas or range limits for 14 species, the presence of 71 species in areas the Atlas designated as “white spots”, new information on 3 species with very limited distribution in Slovenia, and additional corroboration for distribution of 27 species that the Atlas covered.